2022
DOI: 10.1007/s40789-022-00500-5
|View full text |Cite
|
Sign up to set email alerts
|

Petrographic composition of coal within the Benue Trough, Nigeria and a consideration of the paleodepositional setting

Abstract: The petrographic composition of Cretaceous-age coals hosted in the Benue Trough, Nigeria is presented and discussed in terms of the paleodepositional settings that influenced the coal-bearing formations. The Benue Trough is a failed arm of the triple junction of an inland sedimentary basin that extends in a NE-SW direction from the Gulf of Guinea in the south, to the Chad Basin in the north. A total of twenty-nine (29) coal samples were obtained from nineteen coal localities in the Upper (UBT), Middle (MBT), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In the Late Cretaceous, as the Tethys Sea experienced a southward transgression and Atlantic waters moved northwards linking to the Tethys Sea, coal facies developed along the epicontinental seaways and coastal plains across North Africa [138]. The Nigerian Cretaceous-aged coal deposits are lignitic to sub-bituminous to bituminous in rank [143,144], and the coal seams are usually interbedded with bands of shales and mudstones, some of which are oil-bearing. Chukwa et al [145] reported Nigerian coal The Nigerian Cretaceous-aged coal deposits are lignitic to sub-bituminous to bituminous in rank [143,144], and the coal seams are usually interbedded with bands of shales and mudstones, some of which are oil-bearing.…”
Section: Metalliferous Coals From Africamentioning
confidence: 99%
See 4 more Smart Citations
“…In the Late Cretaceous, as the Tethys Sea experienced a southward transgression and Atlantic waters moved northwards linking to the Tethys Sea, coal facies developed along the epicontinental seaways and coastal plains across North Africa [138]. The Nigerian Cretaceous-aged coal deposits are lignitic to sub-bituminous to bituminous in rank [143,144], and the coal seams are usually interbedded with bands of shales and mudstones, some of which are oil-bearing. Chukwa et al [145] reported Nigerian coal The Nigerian Cretaceous-aged coal deposits are lignitic to sub-bituminous to bituminous in rank [143,144], and the coal seams are usually interbedded with bands of shales and mudstones, some of which are oil-bearing.…”
Section: Metalliferous Coals From Africamentioning
confidence: 99%
“…The Nigerian Cretaceous-aged coal deposits are lignitic to sub-bituminous to bituminous in rank [143,144], and the coal seams are usually interbedded with bands of shales and mudstones, some of which are oil-bearing. Chukwa et al [145] reported Nigerian coal The Nigerian Cretaceous-aged coal deposits are lignitic to sub-bituminous to bituminous in rank [143,144], and the coal seams are usually interbedded with bands of shales and mudstones, some of which are oil-bearing. Chukwa et al [145] reported Nigerian coal deposits as 39% bituminous, 49% sub-bituminous, and 12% as lignite.…”
Section: Metalliferous Coals From Africamentioning
confidence: 99%
See 3 more Smart Citations